EXTENSIVE READING; SOME SUGGESTIONS TO ITS TEACHING PROCESS AT STAIN TULUNGAGUNG - Muh. Basuni (Pusat Pengembangan Bahasa IAIN Tulungagung, 2010)
Extensive Reading possesses a very strategic role not only to improve the students’ schemata and language skills, but also to shape the students’ learning culture and attitude. Through reading a wide range of topics, the students will develop their knowledge on various issues. Besides, their varieties of language will also get improved since they will acquire new vocabularies and expression and their correct use in some contexts. Besides, a enjoyable and fun reading activities will finally motivate them to read more books autonomously. This new habit will help a lot in improving the students’ self-learning enthusiasm. This article discusses some characteristic of extensive reading and some practical suggestions to improve the quality of the running Extensive Reading course.